Safe Schools Resource Guide (Distributed by ERIC Clearinghouse, 1994)
This guide was developed in response to a state act. The state's Board of Education was required to develop a list of recommended conflict resolution and mediation materials, models, and curricula that address responsible decision making, the causes and effects of school violence and harassment, cultural diversity, and nonviolent methods for resolving conflict, including peer mediation, and then make the list available to local school administrative units. The guide is intended to assist its users in locating services, materials, and assistance on the topics cited above. It is not intended as a definitive listing of the numerous programs, organizations, books, curricula, training, and other information that are available. The materials are presented in eleven categories: (1) curriculum materials; (2) training; (3) programs or models; (4) books/articles/papers annotated; (5) books/articles/papers not annotated; (6) videos; (7) publishers; (8) organizations; (9) school resource officer program; (10) Safe schools grantees; and (11) intervention/prevention strategies. Two appendices provide criteria for selecting a violence prevention curriculum as well as instructional media conflict resolution materials. (RJM)